MANAJEMEN INTEGRASI ZAKAT MAL DAN PEMBERDAYAAN KEARIFAN LOKAL PERELEK DALAM MENINGKATKAN KESEJAHTERAAN UMAT (Studi Kasus : Masjid Jami Al-Amin Desa Sukawening Kec. Ciwidey Kab. Bandung) - Eep Jamaludin; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Background: The management of Zakat Mal at the village mosque level is often trapped in a traditional paradigm characterized by the absence of formal institutions, lack of transparency, and short-term consumptive distribution patterns. This phenomenon contrasts sharply with the vitality of local wisdom, such as the "Perelek" system, which thrives as a community-based social finance mechanism with participatory and accountable governance.Objective: This study aims to (1) identify and analyze the management gap between the Zakat Mal and "Perelek" systems at the mosque level, and (2) design and propose a synergistic integration model based on the POAC (Planning, Organizing, Actuating, Controlling) framework to optimize the role of Islamic philanthropy in enhancing community welfare holistically and sustainably. Method: Using a qualitative approach with an intrinsic case study strategy at the Al-Amin Jami Mosque, Sukawening Village, Bandung Regency. Data collection was conducted through triangulation via participatory observation, in-depth semi-structured interviews with 15 key informants (mosque board members, muzakki, mustahik), and in-depth analysis of financial documents from the "Perelek" program. Data were analyzed using the interactive model of Miles, Huberman, Saldana. Results: The findings reveal a sharp management dichotomy. Zakat Mal management experiences dysfunction across all POAC aspects: lack of data-based planning, ad-hoc institutionalization, passive-reactive implementation, and non-existent control. Conversely, "Perelek" demonstrates optimal performance with routine planning, organization within the mosque board structure, participatory-responsive implementation, and highly transparent control. The significant economic potential of Zakat Mal from the agricultural and convection sectors remains untapped due to a public trust deficit. Conclusion: It is concluded that the main gap lies in the aspects of organizing and controlling. The proposed integration model is "Functional Differentiation with Convergence of Governance Principles", where "Perelek" is consolidated as a consumptive social safety net, while Zakat Mal is transformed into a productive economic empowerment instrument, fully adopting the transparency and participation principles of "Perelek". Implementing this model requires UPZ legalization, contextual zakat fiqh education, and a transformation of the reporting system.ABSTRAKLatar Belakang: Pengelolaan Zakat Mal di tingkat masjid pedesaan seringkali terperangkap dalam paradigma tradisional yang ditandai dengan ketiadaan kelembagaan formal, minimnya transparansi, dan pola distribusi konsumtif jangka pendek. Fenomena ini berbanding terbalik dengan vitalitas kearifan lokal, seperti sistem “Perelek”, yang justru tumbuh sebagai mekanisme keuangan sosial berbasis komunitas dengan tata kelola partisipatif dan akuntabel. Tujuan: Penelitian ini bertujuan untuk (1) mengidentifikasi dan menganalisis kesenjangan manajemen antara sistem Zakat Mal dan “Perelek” di tingkat masjid, serta (2) merancang dan mengusulkan model integrasi sinergis berbasis kerangka POAC (Planning, Organizing, Actuating, Controlling) untuk mengoptimalkan peran filantropi Islam dalam meningkatkan kesejahteraan umat secara holistik dan berkelanjutan. Metode: Menggunakan pendekatan kualitatif dengan strategi studi kasus intrinsik di Masjid Jami Al-Amin, Desa Sukawening, Kabupaten Bandung. Pengumpulan data dilakukan secara triangulasi melalui observasi partisipatif, wawancara mendalam semi-terstruktur terhadap 15 informan kunci (pengurus DKM, muzakki, mustahik), dan analisis mendalam terhadap dokumen keuangan program “Perelek”. Data dianalisis dengan model interaktif Miles, Huberman, Saldana. Hasil: Temuan mengungkap dikotomi manajemen yang tajam. Pengelolaan Zakat Mal mengalami disfungsi pada seluruh aspek POAC: tidak ada perencanaan berbasis data, kelembagaan yang ad-hoc, pelaksanaan yang pasif-reaktif, dan pengawasan yang nihil. Sebaliknya, “Perelek” menunjukkan kinerja optimal dengan perencanaan rutin, pengorganisasian dalam struktur DKM, pelaksanaan yang partisipatif-responsif, dan pengawasan yang sangat transparan. Potensi ekonomi Zakat Mal dari sektor pertanian dan konveksi yang signifikan tidak tergarap akibat defisit kepercayaan publik. Kesimpulan: Disimpulkan bahwa kesenjangan utama terletak pada aspek kelembagaan (organizing) dan akuntabilitas (controlling). Model integrasi yang diusulkan adalah “Diferensiasi Fungsi dengan Konvergensi Prinsip Tata Kelola”, di mana “Perelek” dikonsolidasikan sebagai jaring pengaman sosial konsumtif, sementara Zakat Mal ditransformasi menjadi instrumen pemberdayaan ekonomi produktif, dengan mengadopsi sepenuhnya prinsip transparansi dan partisipasi dari “Perelek”. Implementasi model ini memerlukan legalisasi UPZ, edukasi fikih zakat kontekstual, dan transformasi sistem pelaporan.